2021
DOI: 10.1101/2021.03.18.435878
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined epigenetic and metabolic inhibition blocks platinum-induced ovarian cancer stem cell enrichment

Abstract: High grade serous ovarian cancer (HGSOC) is the most common and aggressive type of ovarian cancer. Platinum resistance is a common occurrence in HGSOC and a main cause of tumor relapse resulting in high patient mortality rates. Recurrent ovarian cancer is enriched in aldehyde dehydrogenase (ALDH)+ ovarian cancer stem cells (OCSCs), which are resistant to platinum agents. We demonstrated that acute platinum treatment induced a DNA damage-dependent decrease in BRCA1 levels through BRCA1 promoter DNA hypermethyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 70 publications
(152 reference statements)
1
19
0
Order By: Relevance
“…Furthermore, high expression and activity of the ALDH1A isoform strongly correlates with platinum resistant OC cells (810) and negatively correlates with survival of OC patients (11, 12). Our group as well as others have demonstrated that acute treatment of OC cells with platinum-based agents results in enrichment of ALDH+ OCSCs (7, 13, 14). Collectively, the evidence suggests that platinum-induced enrichment of ALDH+ OCSCs contributes to OC recurrence and relapse.…”
Section: Introductionsupporting
confidence: 55%
See 4 more Smart Citations
“…Furthermore, high expression and activity of the ALDH1A isoform strongly correlates with platinum resistant OC cells (810) and negatively correlates with survival of OC patients (11, 12). Our group as well as others have demonstrated that acute treatment of OC cells with platinum-based agents results in enrichment of ALDH+ OCSCs (7, 13, 14). Collectively, the evidence suggests that platinum-induced enrichment of ALDH+ OCSCs contributes to OC recurrence and relapse.…”
Section: Introductionsupporting
confidence: 55%
“…Approximately 24 hours after plating, cells were treated with cisplatin alone or in combination with DMSO or appropriate inhibitors and incubated at 37°C, 5% CO 2 for 16 hours. After the incubation time ALDEFLUOR assay (Stem Cell Technologies, #01700) was performed as described previously (14).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations